2014
DOI: 10.21307/ijssis-2019-050
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Estimating Visual Attention using Electrodermal Activity

Abstract: Electrodermal Activity (EDA) refers to change in the electrical properties of skin during mental exertion caused by tension and agitation. In recent studies, it has been revealed that there is an overlap between the brain activation area where emotion occurs and the brain activation area responsible for attentiveness. Consequently, in this paper we test our hypothesis that, given these findings, visual attention can be estimated via EDA. The results of experiments conducted verify that EDA can be used as an at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Moreover, previous studies have shown that SCRs occur when a human changes their focus of attention [7]. Report 5.1 (See Table II) took place while the teacher was focused on the dashboard, reading students' answers and inspecting the activity of a particular group.…”
Section: 3mentioning
confidence: 99%
“…Moreover, previous studies have shown that SCRs occur when a human changes their focus of attention [7]. Report 5.1 (See Table II) took place while the teacher was focused on the dashboard, reading students' answers and inspecting the activity of a particular group.…”
Section: 3mentioning
confidence: 99%
“…Galvanic skin response (GSR), also known as skin conductance or electro-dermal activity EDA is one of the most sensitive psychophysical indicators [20]. The amounts of sweat secreted in times of arousal is responsible for the changes in skin conductance, and can easily be measured in regions with a high concentration of sweat glands, such as the hands and feet.…”
Section: Electro-dermal Activitymentioning
confidence: 99%
“…Especially reactions to startle stimuli that divert attention with a strong probability, such as a flash of light, create spikes in skin conductance. Even though we cannot conclude on the quality of the emotion (positive/negative), EDA can help to identify changes in attentional patterns [20]. Initial tests we conducted, have shown that the EOG electrodes on MEME glasses can also be used to measure EDA.…”
Section: Electro-dermal Activitymentioning
confidence: 99%
“…The sympathetic nerve system includes the hippocampus, amygdala, and cingulate gyrus; these organs respond to attentiveness, showing a link with emotion. We can also employ sympathetic nervous system information from sweat glands to recognize emotions (Yoshida, et al, 2014). The present study aims to identify the emotion of drivers during speaking in two scenarios (drowsy and non-drowsy).…”
Section: Introductionmentioning
confidence: 99%